Stitch Head : The Ghost of Grotteskew - Bass, Guy; Illustrated by Williamson, Pete (London Stripes, 2012)
The ghost of a villainous ne'er-do-well is haunting the corridors of Castle Grotteskew, gunning for Stitch Head's hear ... and soul. Certain that his heart once belonged to the vicious rogue, Stitch Head's world is torn apart. Will he surrender to the evil ghost and agree to do his bidding?
Include Illustrations
Keywords: Monsters -- Juvenile fiction -- Monsters -- Fiction -- Ghost stories